Tanggungjawab Notaris/PPAT Dalam Pembuatan Akta Jual Beli Tanah Yang Tidak Memenuhi Asas Terang dan Tunai Dalam Kasus Putusan Majelis Pengawas Pusat Notaris Nomor: 04/B/MPPN/VIII/2016 - Charles Delon Tunas; Endang Pandamdari (Jurnal Hukum Adigama, 2019)
Notary / PPAT is an official authorized to make a deed that is often sued for violations such as deeds drawn up and read in front of the buyer not in accordance with the agreement, but the Notary / PPAT continues the buying and selling process. If related to the case in this case, EJ makes AJB in his position as PPAT not as a Notary. The notary is personally responsible for carrying out his duties and positions in each deed making. Based on consideration of the decision of the Notary Central Board of Trustees, that EJ has acted inaccurately and does not safeguard the interests of parties related to legal actions so that EJ is considered to have violated Article 16 Paragraph (1) of the Law and the Article 54 paragraph (1) of the Act because the EJ does not keep a copy deed requested by the seller. MPPN's decision was in accordance with the provisions of UUJN, but the sanctions given by EJ were considered too light so that they did not have a deterrent effect. When acting as a PPAT, based on the provisions of Article 55 of Law No. 1/2006 jo PP No.24 / 2016, PPAT is personally responsible for the implementation of the duties and positions in each deed making. The PPAT is faced with 4 (four) responsibilities, namely in terms of professional, administrative, civil and criminal ethics